Analisis Bauran Pemasaran dalam Meningkatkan Penjualan Produk pada Indomaret Lakipadada Kabupaten Tana Toraja - Halima Banne Ringgi’; Helba Rundupadang; Abedneigo Carter Rambulangi (CV. Ulil Albab Corp, 2024)
This research aims to find out how to increase product sales, this research uses a qualitative descriptive method. Data collection by means of observation, interviews and documentation with shop heads and Indomaret Lakipadada employees. The results obtained from this research are an analysis of Indomaret Lakipadada’s marketing mix using brochures and offering promotional items, and how to attract customer’s attention by being polite to each other, being kind, polite and friendly towards customers and convincing customers that Indomaret Lakipadada oftenholds Promotions.